2015
DOI: 10.1091/mbc.e14-02-0762
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometric expression of mtHsp40 and mtHsp70 modulates mitochondrial morphology and cristae structure via Opa1L cleavage

Abstract: Imbalance between mtHsp40 and mtHsp70 enhances Opa1L cleavage, leading to cristae remodeling and eventual mitochondrial fragmentation and defective OXPHOS. This is important for understanding functional links between chaperone activity of mtHsp40/mtHsp70 and mitochondrial biology at the molecular and cellular levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The excessive SOD1 G93A accumulated may sequester Hsp70, preventing its degradation in the ubiquitin–proteasome pathway [ 109 , 110 ]. Interestingly, Hsp40 and Hsp70 also fulfil important roles in modulating mitochondrial morphology through the clearance of the OPA1 protein [ 111 ]. Although we did not measure the expression of Hsp40 and Hsp70, the decrease in the total OPA1 ( Figure 11 ) and the loss of ubiquitin–proteasome pathway activity evident with the FK2 antibody that recognizes mono- and poly-ubiquitinylated proteins ( Figure 12 ), leads us to speculate that SOD1 G93A may interact at least with the mitochondrial chaperone Hsp70, potentially contributing to the alterations in mitochondrial morphology.…”
Section: Discussionmentioning
confidence: 99%
“…The excessive SOD1 G93A accumulated may sequester Hsp70, preventing its degradation in the ubiquitin–proteasome pathway [ 109 , 110 ]. Interestingly, Hsp40 and Hsp70 also fulfil important roles in modulating mitochondrial morphology through the clearance of the OPA1 protein [ 111 ]. Although we did not measure the expression of Hsp40 and Hsp70, the decrease in the total OPA1 ( Figure 11 ) and the loss of ubiquitin–proteasome pathway activity evident with the FK2 antibody that recognizes mono- and poly-ubiquitinylated proteins ( Figure 12 ), leads us to speculate that SOD1 G93A may interact at least with the mitochondrial chaperone Hsp70, potentially contributing to the alterations in mitochondrial morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence has shown that chaperones and co-chaperones are involved in mitochondrial homeostasis. Tid1 can regulate mitochondrial homeostasis via DNA polymerase γ, dynamin-1-like protein, optic atrophy 1, and CR6-interacting factor 1 [ 58 , 59 , 60 , 61 ]. Importantly, it was noted that only prolonged silencing of Tid1 can significantly affect mtDNA gene expression and OCR [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deregulation of TID-1 impairs its interaction with the mitochondrial dynamin-1-like protein DNM1L, causing fragmentation of the mitochondrial network [ 203 ] and negatively influences the CR6-interacting factor 1 (CRIF1) involved in the proper localization of the OXPHOS subunits into the inner mitochondrial membrane [ 210 ]. Similarly, an imbalance between TID-1 and mtHSP70 may be responsible for the mitochondrial fragmentation seen in patients diagnosed with optic atrophy 1 [ 211 ]. A recent study by Patra et al [ 212 ] linked ataxia and developmental delay in one patient to a homozygous mutation in the TID1 gene (Arg151Thr), which produced a TID-1 variant that was less efficiently imported into the mitochondria and had severely impaired co-chaperone functions.…”
Section: Human Mthsp70 Co-chaperonesmentioning
confidence: 99%